2021
DOI: 10.1101/2021.11.07.467613
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypothalamic GABRA5-positive Neurons Control Obesity via Astrocytic GABA

Abstract: SUMMARYThe lateral hypothalamic area (LHA) regulates food intake and energy expenditure. Although LHA neurons innervate adipose tissues, the identity of neurons that regulate fat is undefined. Here we identify that Gabra5-positive neurons in LHA (GABRA5LHA) polysynaptically project to brown and white adipose tissues in the periphery. GABRA5LHA are a distinct subpopulation of GABAergic neurons and show decreased pacemaker firing in diet-induced obesity (DIO) mouse model. Chemogenetic inhibition of GABRA5LHA sup… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 86 publications
0
16
0
Order By: Relevance
“…Astrocyte reactivity is observed in various pathological contexts under acute or chronic conditions and, in many situations, is reversible ( Escartin et al, 2019 ; 2021 ). Reactive astrocytes are defined as astrocytes that undergo morphological, molecular, and functional remodeling in response to injury, disease, or infection of CNS, including neurodegenerative and demyelinating diseases, epilepsy, trauma, ischemia, infection, cancer, and obesity ( Bedner et al, 2015 ; Brusilow et al, 2010 ; Buckman et al, 2013 ; Escartin et al, 2019 ; 2021 ; Garcia-Caceres et al, 2019 ; Michetti et al, 2019 ; Sa et al, 2022 ; Verkhratsky et al, 2017 ; Xu et al, 2010 ). Glial fibrillary acidic protein (GFAP) is a major protein constituent of astrocytic intermediate filaments and the most widely used marker of reactive astrocytes ( Ben Haim et al, 2015 ; Eng and Ghirnikar, 1994 ).…”
Section: Reactive Astrocytes In the Hypothalamusmentioning
confidence: 99%
See 4 more Smart Citations
“…Astrocyte reactivity is observed in various pathological contexts under acute or chronic conditions and, in many situations, is reversible ( Escartin et al, 2019 ; 2021 ). Reactive astrocytes are defined as astrocytes that undergo morphological, molecular, and functional remodeling in response to injury, disease, or infection of CNS, including neurodegenerative and demyelinating diseases, epilepsy, trauma, ischemia, infection, cancer, and obesity ( Bedner et al, 2015 ; Brusilow et al, 2010 ; Buckman et al, 2013 ; Escartin et al, 2019 ; 2021 ; Garcia-Caceres et al, 2019 ; Michetti et al, 2019 ; Sa et al, 2022 ; Verkhratsky et al, 2017 ; Xu et al, 2010 ). Glial fibrillary acidic protein (GFAP) is a major protein constituent of astrocytic intermediate filaments and the most widely used marker of reactive astrocytes ( Ben Haim et al, 2015 ; Eng and Ghirnikar, 1994 ).…”
Section: Reactive Astrocytes In the Hypothalamusmentioning
confidence: 99%
“…In Wistar rats fed with HFD for 8 weeks, it has been consistently found that apoptosis is significantly increased, whereas synaptic input is significantly decreased in LHA ( Moraes et al, 2009 ). Moreover, neuronal dysfunction and decreased neuronal activity after chronic HFD exposure have been reported ( Moraes et al, 2009 ; Sa et al, 2022 ). Recently, a unique population of GABRA5-positive neurons in LHA has been discovered, and these neurons display pacemaker firing activity, which is decreased after HFD feeding in LHA ( Sa et al, 2022 ).…”
Section: Reactive Astrocytes In the Hypothalamusmentioning
confidence: 99%
See 3 more Smart Citations